Optimizing Rural and Urban Land and Building Tax Receipts in Increasing Local Own Revenue in Enrekang Regency - Eko Soerifto Lodi; Syamsul Alam; Oky Deviany (Jurnal Pemerintahan dan Politik Lokal, 2023)
Regional development in Enrekang Regency depends on certain aspects, one of which is Regional Original Income (PAD). Local revenue considered potential is Rural and Urban Land and Building Tax (PBB-P2), but it needs to be maximized more. This study aimed to determine the government's response in optimizing the receipt of local revenue sourced from Rural and Urban Land and Building Tax (PBB-P2). The research method used is qualitative, with data sources derived from documentation and websites. The results of the study found that the Enrekang Regency government, through the Regional Revenue Agency continues to make efforts to optimize Rural and Urban Land and Building Tax (PBB-P2) revenues by conducting outreach in public spaces and social media, checking and re-data collection, conducting government collaborations, and conducting innovation and evaluation. Optimizing these efforts to maximize Rural and Urban Land and Building Tax (PBB-P2) revenues is possible. This effort also has the potential to affect local revenue in the future.